2021
DOI: 10.1111/ene.14852
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and healthcare utilization of rare neurological diseases in Hong Kong: 2014–2018

Abstract: Background There has been increasing attention focused on the epidemiology of rare diseases (RDs) in recent years. Rare neurological diseases (RNDs) constitute a significant proportion of RDs; however, relevant research is still lacking. Methods A list of ICD‐10 codes corresponding to RNDs was compiled using adaptations from the Orphanet Classification of Rare Diseases, and classified into rare epilepsy, movement‐related, neurocutaneous, neuroimmune, neurometabolic and neurodegenerative, neuromuscular and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The primary outcome of this study was the occurrence of HCC, which was identified by ninth and 10 th Revision of the International Classification of Disease (ICD-9 and ICD-10, respectively): ICD-9 155.0 or 155.2 and the ICD-10 C22.0, C22.8, or C22.9. Both ICD-9 [21][22][23][24][25][26] and ICD-10 [27][28][29] coding are widely adopted in the health care system in Hong Kong. HCC constitutes almost all primary malignant neoplasms of the liver in adults, [30,31] and patients with liver secondary or metastases were excluded by the identification of additional primary cancer coding in combination with coding for liver secondaries.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The primary outcome of this study was the occurrence of HCC, which was identified by ninth and 10 th Revision of the International Classification of Disease (ICD-9 and ICD-10, respectively): ICD-9 155.0 or 155.2 and the ICD-10 C22.0, C22.8, or C22.9. Both ICD-9 [21][22][23][24][25][26] and ICD-10 [27][28][29] coding are widely adopted in the health care system in Hong Kong. HCC constitutes almost all primary malignant neoplasms of the liver in adults, [30,31] and patients with liver secondary or metastases were excluded by the identification of additional primary cancer coding in combination with coding for liver secondaries.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The Irish study estimated a lower overall adult prevalence of 63 per 100,000 in 2013, possibly due to a stricter case definition that used multiple data sources and excluded patients labelled with possible myopathies or neuropathies [20]. Finally, a recent study from Hong Kong of all rare neurological diseases estimated a prevalence of 38 per 100,000 for NMD, but GBS and MG were classified as neuroimmune rather than neuromuscular rare neurological diseases [22]. Overall, these inconsistencies led us to focus more on comparing published estimates for the more common NMD conditions.…”
Section: Overall Nmd Estimatesmentioning
confidence: 99%